Entry Strategy of Bageteria to Polish Market - Bandíková, Miriam; Halík, Jaroslav, 1961-; Lhotáková, Markéta, 1971-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The aim of this work is to develop a business plan that FIN needs to enter the Polish market. SWOT analysis, PESTLE analysis, a questionnaire from Polish respondents and an interview with a Polish businessman are used to achieve relevant results. The results of the research showed that this operation will be beneficial for the company, as the Polish respondents indicated that they would be interested in a company with a similar concept. Based on all the information obtained, it was found that it would be most advantageous for the company to use the direct exporting method, and if the operation is successful, the company would consider opening its own production plant in Poland.
Vedoucí práce: Jaroslav Halík
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses